Early child development in China : breaking the cycle of poverty and improving future competitiveness - Wu, Kin Bing, 1951- (Directions in development (Washington, D.C.). Countries and regions., 2012)
In China, despite the introduction of economic reforms that have lifted millions out of poverty, the income gap between rural and urban areas remains wide. There is a growing realization in policy circles that economic growth alone cannot reduce absolute poverty and inequality, and that investment in human development is needed to sustain growth and improve social cohesion. Prepared as a collaborative study between the World Bank and China's National Population and Family Planning Commission, Early Child Development in China: Breaking the Cycle of Poverty and Improving Future Competitiveness a.